Voting System with Artificial Intelligence and Blockchain - Bhujel, Sudip; Bhattarai, Sulove; Neupane, Nikesh; Adhikari, Santosh (KEC Journal of Science and Engineering, 2023)
Voting is an essential democratic practice of finding out the public opinion about the policy of candidates. For free and fair voting procedure, a systematic voting system must be designed. Today almost every aspect of our lives is aided by the technology and with the advancement in the technology, the voting system can be upgraded to AI Voting System from the traditional ballot paper system with fair results. This paper discusses designing of voting system with best possible secure way. AI and Blockchain are two underlying technologies used to achieve secure and fraud-free voting environment. Face recognition being the source of truth for authentication and authorization and Blockchain encryption being the safest way to store and read electronic ballot make system ideal. All data related to voting are encrypted in Blockchain decentralized network. In blockchain technology, each process is controlled by Smart Contract, they are trackable and irreversible.